(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Health problems are very paramount in any place, especially in the province of Nueva Ecija. Therefore, this study intends to raise awareness in the community about the health status of the Novo Ecijano’s and serves as a link among the community-based health workers of each municipality and city health offices. It includes a Thematic Map feature to monitor the health status and generate reports needed by the Provincial Heath Office for the prevention of the different diseases present in a number of its population. This also determines the needed stock of vaccines based on the demand history in a municipality or city that will help in preventing the specific diseases with more cases. Aside from this, updates about the health awareness programs can be uploaded and seen online. A mobile application for the community health workers was also integrated in the system to send a notification on the next follow-up consultation and scheduled vaccines for the patient. Based on the findings, all the features integrated in the project were rated as very satisfied and satisfied. Evidently, the integration of the different technologies solves the pressing public health concerns faced by the province of Nueva Ecija.